Fuzzy Distance-Based Approach for the Assessment and Selection of Programming Languages: Fuzzy-Based Hybrid Approach for Selection of PL - Raheja, Supriya; Garg, Rakesh (International journal of decision support system technology, 2023)
The desire to develop software with more and more functionalities to make human work easier pushes the industry towards developing various programming languages. The existence of the various programming languages in today's scenario raises the need for their evaluation. The motive of this research is the development of a deterministic decision support framework to solve the object-oriented programming (OOP) language's selection problem. In the present study, OOP language's selection problem is modeled as a multi-criteria decision-making, and a novel fuzzy-distance based approach is anticipated to solve the same. To demonstrate the working of developed framework, a case study consisting of the selection of seven programming languages is presented. The results of this study depict that Python is the most preferred language compared to other object-oriented programming languages. Selection of OOP languages helps to select the most appropriate language, which provides better opportunities in the business domain and will result in high success for engineering students.